The Effectiveness of Instructional Scaffolding Strategy in Developing Social Interaction of Eleventh-Grade Students in The Subject of History - Haji, Sattar Jabbar; Safar, Imad Ali; Mostafa, Dilkhaz Shekhomar (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed to investigate the effectiveness of instructional scaffolding strategy in developing social interaction of eleventh-grade students in the subject of history. To achieve the aim, the experimental approach for two equivalent group were used, an experimental group taught according to instructional scaffolding strategy, and the control one according to traditional method. The research sample consisted of (54) female students in the eleventh class of high school for the academic year (2021-2022), they were chosen randomly, from two schools (Shiladze and Sirie), the researchers distributed the teaching method to the two schools randomly, the experimental group was represented by class (A) with (29) students, and class (C) with (25) students in the control group. The researchers conducted the equivalence between the students of the two groups in the variables: (chronological age, intelligence degree, and social interaction). To determine the level of social interaction, the researchers used a scale consisting of (30) items, which was applied to the students (pre- test and post-test). And after applying the statistical analysis using the (t-test) for two independent samples (t. test), the results showed that there were statistically significant differences between the arithmetic mean degrees of the development difference of the experimental and control groups in the social interaction, the Calculated T. Value (3.642) was greater than schedule T. value (2.34) at the significant level (0.05), and in favor of experimental group which used instructional scaffolding strategy. In the light of the results, a number of recommendations recommended by the researchers, most important is Urging history teachers in the preparatory education stage to use the instructional scaffolding strategy in teaching, and introduce the theoretical and practical framework for the instructional scaffolding strategy in the content of the subject of methods of teaching history for the faculties of education and basic education in Iraqi universities.
Keywords: Instructional Scaffolding Strategy; Social interaction; Preparatory education stage; History subject